Estimating Shadow Wage Rates for Economic Project Appraisal (The Pakistan Development Review, 2004)
One of the central concerns in cost benefit analysis is the adjustment of distortions in markets to provide a better guide to a more effective allocation of scarce resources. The objectives of this paper are to develop a model for the estimation of the shadow wage rate (SWR) for groups of occupations and to estimate the SWRs for the major groups of occupations in Australia. The main findings of the analysis indicate that estimated SWRs for major groups of occupations are different from the corresponding market wage rates, and that estimated SWRs of the groups are different. The results of the study demonstrate the importance of estimation of the SWR as a part of the appraisal process of investment projects. The ratio analysis indicates the significance of the difference between SWR and market wage rate, which is recommended to be adjusted is economic analysis of projects.